Biological control of basal stem rot disease in mature oil palm (Elaeis guineensis) in inland and peat soil - Ridzuan, Nur Izzati (2022)
Oil palm is the main commodity crop cultivated in Malaysia and has made significant contributions to the economies of Malaysia and Indonesia. However, there is a major problem in oil palm, the basal stem rot (BSR) disease caused by Ganoderma boninense. This is a serious threat to the oil palm industry as it reduces oil palm yield and shortens the economic lifespan of the crop. In order to control this disease, this present study evaluated the efficacy of Trichoderma spp. as a biological control agent (BCA) through the application of different types of bioorganic fertilizers at selected oil palm estates in Palong, Pahang and Tanjung Karang, Selangor with different palm ages and soil types.